Dose escalation study of the HLA-A2-WT1 CD3 bispecific antibody RO7283420 in relapsed/refractory acute myeloid leukemia - Martin Hutchings; Koorosh Korfi; Pau Montesinos; Armando Santoro; Hsin-An Hou; Pilar Martinez-Sanchez; Susana Vives; Sara Galimberti; Tsai-Yun Chen; Marco Frigeni; Sylvain Garciaz; Olga Salamero Garcia; et al. (Blood Neoplasia, 2025)
Abstract: A novel T-cell bispecific antibody (TCB), RO7283420, engaging CD3 and the HLA-A2-Wilms tumor protein 1 complex, was evaluated in this phase 1 study to characterize safety and tolerability, determine the maximum tolerated dose (MTD), and recommend a phase 2 dose for patients with relapsed/refractory acute myeloid leukemia in 2 groups: hematologic (group I, n = 57) and molecular (group 2, n = 5) relapse. In group I, 51 received RO7283420 intravenously (IV) and 6 subcutaneously. The IV doses ranged from 0.15-4 mg (flat; n = 13), 3-18 mg (step-up; n = 34) every 3 weeks, or 9 mg weekly (step-up; n = 4). The MTD was 1/3/12 mg every 3 weeks. The most frequent adverse event in the overall population was cytokine release syndrome (61.3%) with grade ≥3 recorded in 9.7% of patients. Twelve dose-limiting toxicities were reported in 11 patients and 12 (19.4%) grade 5 adverse events, including 1 hemophagocytic lymphohistiocytosis case related to RO7283420. Among the 42 efficacy-evaluable IV patients in group I, 4.8% achieved complete remission (CR), and 2.4% achieved CR with incomplete hematologic recovery. RO7283420 induced pharmacodynamic changes in peripheral blood (PB) at doses ≥1 mg, including significant T-cell activation and expansion in the PB and bone marrow (BM). Significant associations were found between blast reduction and baseline immunophenotype, including lower regulatory T cells and higher non-exhausted CD8+ T cells in BM. Although dose escalation was discontinued because of limited efficacy and lack of an exposure-BM response relationship, the observed pharmacodynamics underscore the promising potential of this class of TCBs targeting intracellular antigens. This trial was registered at www.clinicaltrials.gov as #NCT04580121.